Ogólna sanatio in radice udzielona przez Stolicę Apostolską (kan. 1165 §1). Przykład uważnienia małżeństw zawartych bez zachowania formy kanonicznej w Ordynariacie Polowym - Dohnalik, Jan (Ius Matrimoniale, 2018)
The article describes an important issue of the radical sanation granted to numerous couples by the Holy See. According to the can. 1165 diocesan bishop can convalidate in radice only in individual cases, while the Holy See is subject to no restrictions. Although the Holy See has granted general sanation on several occasions, the canonical procedures to apply for such a grace have not been sufficiently explained in literature. Therefore a profound study of the recently given radical sanation to the marriages contracted in the Military Ordinariate of Poland could fill in the abovementioned gap. In 1991-2011 many military chaplains assisted marriages where neither party was subject to their jurisdiction. Those chaplains lacked due delegation as having come from territorial dioceses they failed to understand the requirements of personal jurisdiction. Following restoring the order stipulated by the can. 1110 CIC, the Military Bishop decided to apply to the Holy See of marriages contracted in the first twenty years of the renewed Ordinariate. There was gathered documentation consisting of: a summary of a survey conducted among military chaplains concerning the size of the phenomenon; sentences of ecclesiastical tribunals; a record of website addresses reporting marriage validity problem in the Military Ordinariate; supporting letters signed by certain prominent Polish bishops. Upon delivery of the dossier in 2016, the Congregation for the Divine Cult authorized by Pope Francis issued the radical sanation rescript in December 2017. Not only does the study touches upon a theorical problem, but also provides practical advice for proceeding in similar cases.